Influences of Rainfall and Antecedent Precipitation Index on Surface Runoff Generation in Na Luang Sub-Watershed, Nan Province - Lekprasoet, Ratchaneekorn; Tuankrua, Venus; Kheereemangkla, Yutthaphong (Thai Journal of Science and Technology, 2022)
Rainfall and antecedent precipitation index (API) can be used as indicators or criteria for surface runoff. This study found that the average annual rainfall (2018-2019) was 989.40 mm. When daily antecedent precipitation index (APIt) was greater than the critical antecedent precipitation index calculated by saturated soil moisture (CAPIsat), it was indicated that there were surface runoff events in the natural forests and agricultural watersheds as 16 and 71 times, respectively. The averages of surface runoff were approximately 20.39 and 37.10 mm per time, respectively. The 9-day accumulated rainfall levels were greater or equal to 87.39 and 49.54 mm, respectively. Moreover, the daily antecedent precipitation indexes were 211.44 and 200.02 mm, respectively. The natural forest watersheds occurred surface runoff less than agricultural watersheds as 81.89 percent.